2017
DOI: 10.1021/acs.jpcb.7b10857
|View full text |Cite
|
Sign up to set email alerts
|

Structure of ZnCl2 Melt. Part II: Fragile-to-Strong Transition in a Tetrahedral Liquid

Abstract: The fraction of edge- and corner-sharing tetrahedra in liquid ZnCl is quantified as a function of temperature using Raman spectroscopy and ab initio molecular dynamic simulations. Two distinct regimes are found in the temperature dependence of the change in these structural units. This behavior is consistent with the existence of a fragile-to-strong transition in liquid ZnCl as suggested by calorimetric and viscosity measurements. The structural origin of this transition is rationalized in terms of a constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…For Ge 15 Te 85 and tellurium, the density increase is more pronounced, in accordance with the sharper F‐S transition. Density data for the Ge‐Se system indicate that such transitions are prevalent in the Ge‐rich portion of the binary system, including GeSe 2 as previously suggested . This is consistent with viscosity data indicating F‐S transitions in all these Ge‐rich compositions .…”
Section: Fragile‐to‐strong Transitionssupporting
confidence: 89%
See 1 more Smart Citation
“…For Ge 15 Te 85 and tellurium, the density increase is more pronounced, in accordance with the sharper F‐S transition. Density data for the Ge‐Se system indicate that such transitions are prevalent in the Ge‐rich portion of the binary system, including GeSe 2 as previously suggested . This is consistent with viscosity data indicating F‐S transitions in all these Ge‐rich compositions .…”
Section: Fragile‐to‐strong Transitionssupporting
confidence: 89%
“…Density data for the Ge-Se system indicate that such transitions are prevalent in the Ge-rich portion of the binary system, including GeSe 2 as previously suggested. 8,60 This is consistent with viscosity data indicating F-S transitions in all F I G U R E 2 Maxima in thermodynamic response functions indicative of liquid-liquid phase transitions in chalcogenide systems. Arrows represent the melting point or liquidus temperature for each system.…”
Section: Fragile-to-strong Transitionssupporting
confidence: 84%
“…Non-PCMs are characterized by slow crystallization kinetics (13) and good glass-forming abilities in terms of the Turnbull parameter T g /T l ≥ 0.6, where T g and T l are the glass transition temperature at a conventional rate (e.g., 20 K/min) and the liquidus temperature, respectively. Turnbull (37) showed that T g /T l close to 2/3 is the criterion for good glass formers [T g /T l = 0.6 for GeSe (38), 0.61 for Ge 15 Te 85 (39), and 0.68 for GeSe 2 (40)]. On the contrary, PCMs have T g /T l ~ 0.5, indicative of poor glass-forming T (K) abilities (35,38).…”
Section: Resultsmentioning
confidence: 99%
“…For PCM applications, GeTe, on July 4, 2020 http://advances.sciencemag.org/ Downloaded from Ge 2 Sb 2 Te 5 , and AIST crystallize on a time scale of nanoseconds (~10 to 100 ns) at elevated temperatures (5,10). By contrast, non-PCMs like Ge 15 Te 85 , GeSe, and GeSe 2 crystallize much more slowly (36,40), rendering them unsuitable for phase-change memory applications. According to the classical theory of nucleation and growth, the nucleation rate I s and crystal growth velocity u can be respectively expressed as (50-52)…”
Section: Discussionmentioning
confidence: 99%
“…We have also examined the fragility index of the homogenized Ge–Se melts using the Moynihan approach . In this approach one examines the scan rate ( q = d T /d t ) dependence of T g in a DSC experiment.…”
Section: Fragility Index Of Gexse100−x Meltsmentioning
confidence: 99%